Beyond piecewise methods: Modular integrated hydroeconomic modeling to assess the impacts of adaptation policies in irrigated agriculture. (February 2021) - Pérez-Blanco, C. Dionisio; González-López, Héctor; Hrast-Essenfelder, Arthur
Abstract: The accurate understanding of the human-modified water cycle calls for a detailed representation of human and water systems, including relevant non-linearities, and of the feedback responses between them. This paper couples a microeconomic Positive Multi-Attribute Utility Programming model with a Hydrologic Modeling System (HEC-HMS) with the objective of incorporating the behavior and adaptive responses of human agents into the representation of the human-modified water cycle. The coupling occurs in a sequential fashion using bidirectional protocols that represent the feedback responses between the microeconomic and hydrologic modules through common spatial elements and variables. The proposed model is illustrated with an application to agricultural water management in the Upper Tagus River Basin in Spain. The non-linear responses observed in the modeled human-water system suggest that strengthening the agricultural water allocation constraint can avert or delay drought negative environmental impacts with a less-than-proportional yet incremental impact on Gross Value Added and employment. Highlights: Human-water systems modeling should account for non-linearities and two-way feedbacks. We couple a microeconomic mathematical programming model with HEC-HMS. The coupling relies on modularity and sequential bidirectional protocols. Non-linear farm responses have non-trivial impacts on the human-modified water cycle. Hydroeconomic modeling needs to go beyond piecewise approximations to human agency.